A CONCEPTUAL ANALYSIS ON DEVELOPMENT OF RURAL VILLAGES WITH SCARCLY RESOURCES IN PRAKASAM DIST, ANDHRA PRADESH - Shaik Khadar Basha (International Journal of Research Science and Management, 2017)
Most of the people (nearly 70%) lived in rural villages. Generally we can’t imagine the world without rural villages. So the study explains, development of rural villages with scarcely resources in prakasam dist Andhra Pradesh and explains how to utilization of scarcely resources effectively in rural villages. Rural Development means it is process in all round development of rural area based on scientific utilization of India's natural resources. With this aim, several efforts were made at rural development to better the socio-economic lot of villagers from ancient times to British period. The main objective of the study is to develop the rural villages with available limited resources in prakasam dist Andhra Pradesh state. The purpose of the study is to find out and evaluate the scarcely resources in each every backward rural villages in prakasam dist, AP and work towards to effective utilization of these resources for better development of rural areas. It might be caused for economic growth and economic development of rural villages in the country. After completion of the study we can get the result of how to develop rural villages with scarcely resources in prakasam dist, Andhra Pradesh and finally we get full awareness and knowledge about scarcely resources in rural areas.